The State-Charity Disparity and the 2017 Tax Law - Daniel Hemel (Washington University Journal of Law & Policy, 2019)
This is an edited version of a speech given at the state tax symposium. The author first gives an overview of how the 2017 tax bill changed the treatment of state and local taxes which are no longer deductible to the extent said taxes exceed $10,000. The author then contrasts this to the treatment of charitable contributions which remain deductible. The author considers the similar functions undertaken by charities and state governments and concludes there is little justification for their divergent treatment.
Keywords: Tax; Tax law; SALT; State and local taxes; charitable contributions; IRS; 2017 tax law